Ecology and Diversity of Ectomycorrhiza in moist Tropical Forest of Sunsari District, Eastern Nepal - Shrestha, Sabitri; Gautam, Tilak Prasad; Mandal, Tej Narayan; Aryal, Hari Prasad (Journal of Institute of Science and Technology, 2021)
An ectomycorrhiza plays a vital role in the maintenance and strengthening the forest ecosystems and diversity. This study attempts to assess the ecology and diversity of ectomycorrhiza in tropical Sal (Shorea robusta Gaertn.) forest in Sunsari district, eastern Nepal. The collection of ectomycorrhiza was carried out from June to September (rainy season) for the year 2019-2020. A total of 18 species of ectomycorrhiza belonging to 12 genera and 7 families were collected. Russulaceae was found to be the dominant family representing 7 species. As per the diversity indices, the Shannon Weiner index and Simpson’s index were found to be 2.60 and 0.913, respectively indicating a higher value for the index of diversity. The results conclude that the moist tropical forest of Sunsari district is rich in ectomycorrhizal fungi, which consequently may provide a great opportunity for nutrient absorption